Multilayer Nanofilms via Inkjet Printing for Stabilizing Growth Factor and Designing Desired Cell Developments. Issue 14 (24th April 2017) - Choi, Moonhyun; Park, Hee Ho; Choi, Daheui; Han, Uiyoung; Park, Tai Hyun; Lee, Hwankyu; Park, Juhyun; Hong, Jinkee
Abstract : Biologically versatile basic fibroblast growth factor (bFGF), well known for roles of signaling molecules between cells and regulating various cellular processes, has been proven to utilize specific functionalities. However, the remarkable functions are inclinable to dwindle with decrease of bFGFs' activity. In nanoscale, developing thin films with intrinsic characteristics of building molecules can facilitate handling various materials for desired purposes. Fabricating nanofilm and handling sensitive materials without detriment to activity via highly productive manufacturing are significant for practical uses in the field of biomedical applications. Herein, a multilayered nanofilm fabricating system is developed by inkjet printing to incorporate bFGF successfully. It is demonstrated that water mixed with glycerol as biological ink maintains stability of bFGFs through simulation and experimental study. With highly stable bFGFs, the proliferation of human dermal fibroblast is enhanced and the undifferentiated state of induced pluripotent stem cell is maintained by the controlled release of bFGF. Abstract : Nanofilm incorporating basic fibroblast growth factors (bFGFs) are fabricated using inkjet printing and layer‐by‐layer assembly. During fabrication process, activity of bFGFs is highly stabilized by mixture of glycerol and water (3:7). The bFGFs released from nanofilm have an effect on a various kinds of cells, such as proliferation of human dermal fibroblast or differentiation of induced pluripotent stem cell.